Hypergravity is more challenging than microgravity for the human sensorimotor system - Loïc Chomienne; Patrick Sainton; Fabrice R. Sarlegna; Lionel Bringoux (npj Microgravity)
Abstract The importance of gravity for human motor control is well established, but it remains unclear how the central nervous system accounts for gravitational changes to perform complex motor skills. We tested the hypothesis that microgravity and hypergravity have distinct effects on the neuromuscular control of reaching movements compared to normogravity. To test the influence of gravity levels on sensorimotor planning and control, participants (n = 9) had to reach toward visual targets during parabolic flights. Whole-body kinematics and muscular activity were adjusted in microgravity, allowing arm reaching to be as accurate as in normogravity. However, we observed in hypergravity a systematic undershooting, which likely resulted from a lack of reorganization of muscle activations. While new studies are necessary to clarify whether hypergravity impairs the internal model of limb dynamics, our findings provide new evidence that hypergravity creates a challenge that the human sensorimotor system is unable to solve in the short term.